CA-1, a novel phosphoprotein, interacts with the promoter of the cab140 gene in Arabidopsis and is undetectable in det1 mutant seedlings. - Sun, L (1993)
We have identified and partially purified a DNA binding protein from Arabidopsis that interacts specifically with the phytochrome-responsive promoter of the Arabidopsis cab140 gene. Promoter deletion analyses in transgenic tobacco showed that, if a region that includes the sequence interacting with this protein was deleted, both expression and phytochrome responsiveness were lost. The protein protected a cytosine- and adenine-rich region from DNase I digestion, and therefore it has been called Ca-1. CA-1 was shown to be a phosphoprotein, and dephosphorylation changed the migration of the protein-DNA complex in DNA mobility shift assays. The data suggested that the protein has an apparent molecular weight of 70,000. The CA-1-protected region of the cab140 promoter included an ACGT motif that has been found in the target sequences of a number of bZIP transcription factors, but the binding behavior of CA-1 differed from those factors. CA-1 binding activity was present in plants grown in either white light or darkness, and no differences in the binding activity were detected in the dark-grown plants after short red or white light treatments. However, the CA-1 binding activity was not detectable in extracts of seedlings bearing the det1 mutation grown in the dark and given the same illumination treatments as wild type. In contrast to wild type, the mutant seedlings express cab RNA at a high level when grown in complete darkness, and we found no further increase in cab140 mRNA in response to brief red illumination. The lack of CA-1 activity in the det1 mutant suggests that it may function as a transcriptional repressor regulating the expression of the cab140 gene in Arabidopsis.